Fotografia w polskim systemie prasowym - Mariański, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
Press photography is not a frequent subject of press specialists’ considerations although it is an inseparable component of contemporary newspapers and magazines. The great part photography plays in the contemporary world in conveying information, spreading knowledge, shaping opinions and social, political and cultural attitudes is frequently forgotten. It should be sought in its universal character on the one hand and in its imminent authenticity and utter believability of its presentations on the other. Together with woodcuts and lithographs it played a supporting part. However, it has won certain privileges. It was copied in high circulation periodicals and wandered the world in thousands of copies thus gaining importance. The press has not only contributed to photography becoming common. In many instances it has preserved photographs for the posterity as an uncountable number of daguerreotypes and old photographs have been lost or destroyed forever and the only evidence of their existence have been their printed versions in old weeklies and albums, as well as separate prints.